ANALISIS KEUNTUNGAN USAHA PENJUALAN BUAH NENAS PADA KENDARAAN RODA EMPAT DI JALAN RINGROAD SATU KOTA MANADO (Profit Analysis of the Pineapple Fruit Sales Business in Four Wheeled Vehicle in Ringroad Satu Road Manado City) - Helena Langie; Jelly R. D. Lumingkewas; Theodora M. Katiandagho (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The objective of this research is to analyze the profit and return of cost ratio of the pineapple fruit sales effort on a four-wheeled vehicle on the Ringroad One Street of Manado City. The research method used in the case study method, the data collected in this study are: primary data and secondary data. Primary data obtained through direct interviews using a list of questions and in-depth interviews with pineapple fruit sellers. Sampling was used purposive sampling. The number of respondents were 8 pineapple fruit sellers. Data were analyzed descriptively and analysis of profit and return of cost ratio. The research results showed that the average total revenue of each responden was Rp. 44,258,250 and the total average cost per respondent was Rp.32,554,312 with an average profit per respondent was Rp.11,703,938, business feasibility index was 1.36.Keywords: Profit Analysis, Pineapple Fruit Sales Business, Business Feasibility Index